First jack-up rig load-out in Viet Nam - Dung, Ngo Tuan (Petrovietnam Journal, 2013)
This paper presents the design concept and operation results of load-out for the jack-up rig LTI model 116E built on two skid beams (without dry dock facilities). It was the first attempt to build a jack-up rig, almost completely, on two skid beams on the ground and load-out it using the submersible barge “Giant 2”. The major characteristics of load-out structures, which depend on a jack-up rig configuration composed of general jack-up rig type hull and other structures, were its heavy weight of approximately 9,000 metric tons and long length of 74.09m compared to breadth and depth, i.e. x 62.79 x 7.95m. So, special consideration was required for safe load-out operation compared to previous load-out of other offshore structures (jackets, topsides) where the weight was less than 4,000 - 5,500 metric tons. The strength and longitudinal deflection of the jack-up rig were carefully analysed with appropriate weight distribution. All facilities for load-out including ground foundation, strain jack system and pulling system were designed based on the results of this analysis and the friction force between the skid way and hull supports (skid shoe). The ballasting operation for the barge was controlled by the control system (PLC) in the control room. Relative deflection in way of jack-up rig was monitored during the load-out operation. The motion of the jack-up rig during the load-out process, towing to float-off site and float-off phase were analysed and compared to model test results. The load-out concept and methodologies described here are verified through the successful load-out operation of the first jack-up rig project in Viet Nam. The concept and experience gained can be adopted for the load-out design of extra-heavy structures where the weight is more than 15,000 metric tons. Guidelines for the development of an efficient construction method for offshore and ship type structures are also suggested for future application of this concept.